Studies on the interaction of Na+ ion with binary mixture of carbonate-ester solvents: A density functional theory approach. Issue 1 (March 2021) - Tiwari, Sakshi; Gupta, Abhishek Kumar; Gupta, Shivani; Gupta, Sarvesh Kumar; Chaurasia, Sujeet Kumar
Abstract: The advancement of sodium-ion batteries as an alternative to lithium-ion batteries presents a viable way to make energy storage cost-efficient. However, the inherent properties of Na + are not quite well understood as it is for Li +, which also include solvation of Na + in non-aqueous electrolyte for its application in electrochemical devices. Here, a comprehensive study of Na + solvation in the binary mixture of ethylene carbonate (EC) and propylene carbonate (PC) in different ratios is reported, using density functional theory calculation. The optimised structure of cluster of binary mixture EC-PC-Na + in three different ratios (1:1, 2:1 and 3:1) of EC: PC is analysed. Binding and Gibbs free energy of Na + solvated by EC and PC and charge on Na + is calculated. The calculated results favour the stability of binary mixtures containing higher concentration of ethylene carbonate. In infrared (IR) vibrational spectra, substantial changes are observed in the IR active modes of the solvent because of cation-solvent interaction.